2008
DOI: 10.1177/154230500806200111
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Ethnographic Study of Sources and Definitions of Theological Reflection in Pastoral Care and Counseling

Abstract: What are the sources and definitions of theological reflection developed by Canadian practitioners of pastoral care and counseling? This study is part of a larger qualitative research project on theological reflection. This research reviews the literature, describes the ethnographic method, and presents the findings with a sample of 75. Main sources are sacred texts, personal experience, experiences of clients, and traditions of faith group. Definitions are meaning making, discovering the divine and disciplesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Could there be a partnership around spiritual care where each shares their resources? The findings in this study and the study on theological reflection (O"Connor & Meakes, 2008) invite such collaboration.…”
Section: Discussion Of Data and Implications For Practicementioning
confidence: 58%
See 3 more Smart Citations
“…Could there be a partnership around spiritual care where each shares their resources? The findings in this study and the study on theological reflection (O"Connor & Meakes, 2008) invite such collaboration.…”
Section: Discussion Of Data and Implications For Practicementioning
confidence: 58%
“…The researchers struggled to systematize the findings. After a number of attempts, the primary investigator (TOC) used the themes from the research study on sources and definitions in theological reflection (O"Connor & Meakes, 2008) in a deductive manner to code the data from this study on professionals who are not chaplains. Similarities and differences were noted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the 75 participants articulate three goals: understanding, integration and transformation. In another article from the same study, (O'Connor and Meakes, 2007), they found three definitions with a variety of sources. Neither of these two articles by Meakes (2006, 2007) mention importance of theological reflection to identity or the conversation partners.…”
Section: Review Of the Literaturementioning
confidence: 99%